A high-temperature corrosion-resistant coating process for a glass fiber industry drawing cooler

CN118639229BActive Publication Date: 2026-10-20NANTONG GAOXIN ANTIWEAR MATERIALS TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410721061.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2026-10-20
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

铜片尺寸为80*30*3mm, 由于拉丝过程有腐蚀性气体,铜片的上边缘及两侧边会腐蚀损坏,寿命在10天左右,表面镀镍的话,寿命在30-60天左右,更换频繁给连续生产带来了很多不便

Benefits of technology

(1)本发明中,通过对冷却器用的铜片的边缘采用镍基激光熔覆工艺进行处理,具体是通过特定的激光熔覆参数设定和激光熔覆粉末相结合,有效增强了冷却器铜片的边缘防腐的性能;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a high-temperature corrosion-resistant coating process for a cooler used in a glass fiber industry drawing process, which comprises the following steps: (1) treating the edges of copper sheets used in the cooler by a nickel-based laser cladding process; (2) treating the two sides of the copper sheets used in the cooler by a supersonic spraying process; and (3) treating the surfaces of the copper sheets used in the cooler by a PVD ion sputtering plating process. The high-temperature corrosion-resistant coating process for the copper sheets of the cooler used in the glass fiber industry drawing process has the advantages that the edges of the copper sheets used in the cooler and the two sides of the copper sheets used in the cooler are respectively treated by a nickel-based laser cladding process and a supersonic spraying process, and finally, the surfaces of the copper sheets are treated by a PVD ion sputtering plating process, so that the copper sheets are assembled to the cooler after corrosion resistance of the surfaces of the copper sheets is improved, the corrosion resistance and wear resistance of the cooler are improved, and the service life of the cooler is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to surface anti-corrosion coating technology, specifically relating to a high-temperature anti-corrosion coating process for coolers used in fiber drawing in the glass fiber industry. Background Technology

[0002] In the glass fiber drawing process, using various types of fiber root coolers near the glass fiber roots at the bottom of the stencil is an effective measure to stabilize the drawing operation, increase drawing speed, and boost production. Especially with the adoption of perforated stencils, fiber root coolers are indispensable components to ensure uniform temperature between the inner and outer perforations.

[0003] Existing wire drawing coolers typically use 18 copper fins arranged in a comb pattern, with a cooling water pipe on one side of each fin. The copper fins are 80*30*3mm in size. Due to the corrosive gases produced during the wire drawing process, the upper and side edges of the copper fins corrode and are damaged, resulting in a lifespan of about 10 days. If the surface is nickel-plated, the lifespan is about 30-60 days. Frequent replacements cause many inconveniences for continuous production. Summary of the Invention

[0004] Purpose of the invention: This invention addresses the shortcomings of existing technologies by proposing a high-temperature anti-corrosion coating process for coolers used in fiberglass drawing.

[0005] Technical solution: The high-temperature anti-corrosion coating process for coolers used in fiberglass drawing according to the present invention includes: (1) The edges of the copper sheets used in the cooler are treated with a nickel-based laser cladding process; (2) The copper sheets used in the cooler are treated with a supersonic spraying process on both sides; (3) The surface of the copper sheet used in the cooler is treated with PVD ion sputtering coating process.

[0006] In some embodiments, the nickel-based laser cladding process specifically includes: S1. Grind the surface of the copper sheet used in the cooler to remove the surface oxide scale and stains. Clean the surface with anhydrous ethanol and acetone, dry it, and protect the surface that does not require laser cladding. S2. The dried laser cladding powder is placed into the powder feeder and continuously fed using a coaxial powder feeding system to complete the laser cladding on the upper edge and adjacent side edges of the copper sheet. The cladding thickness is 0.5-0.8mm.

[0007] S3. The cladding coating is ground and polished, and the thickness of the coating after grinding is 0.4-0.6mm.

[0008] In some implementations, the laser cladding process parameters are as follows: laser power of 1500W-2000W, scanning speed of 200-800mm / min, laser cladding powder feeding amount of 20-30g / min, protective gas of argon, and gas flow rate of 12-15L / min.

[0009] In some embodiments, the laser cladding powder comprises the following materials by weight percentage: Ni: 60-70%, Mo: 2.8-5%, Cr: 15-25%, Ti: 0.75-1.2%, Mn: 4-6%, with the remainder being Fe and unavoidable impurities, and the powder particle size being 150-450 mesh.

[0010] In some embodiments, the supersonic spraying process specifically includes: S1. Clean both sides of the copper sheet used in the cooler with anhydrous ethanol and acetone, and then dry it. S2. Place the dried supersonic spraying powder into the supersonic spraying equipment to complete the supersonic spraying, with a spraying thickness of 0.3-0.4 mm. S3. Use specialized grinding equipment to grind the sprayed surface smooth.

[0011] In some embodiments, the process parameters for supersonic spraying are: compressed air pressure 2-3 MPa, propane pressure 0.5-1 MPa, and nitrogen pressure 0.1-0.3 MPa.

[0012] In some embodiments, the supersonic spray powder comprises the following materials by weight percentage: Ni: 60-75%, Cr: 10-20%, TIC and WC: 10-20%.

[0013] In some embodiments, the PVD ion sputtering coating process specifically includes: A PVD magnetron sputtering device was used to deposit a film on the surface of the copper sheet used in the cooler, with a film thickness of 3-5 μm.

[0014] In some embodiments, the PVD magnetron sputtering coating uses a titanium aluminum nitride target.

[0015] In some embodiments, the operating parameters of the PVD magnetron sputtering equipment are as follows: vacuum degree is 0.3 × 10⁻⁶. -5 ~0.8×10 -5 Torr, bias voltage 60-100V, target current 5-8A.

[0016] Beneficial effects: The beneficial effects of this invention are as follows: (1) In this invention, the edges of the copper sheets used in the cooler are treated by a nickel-based laser cladding process. Specifically, the corrosion resistance of the edges of the copper sheets in the cooler is effectively enhanced by setting specific laser cladding parameters and combining laser cladding powder. (2) In this invention, the two sides of the copper sheet used in the cooler are treated by supersonic spraying process. Specifically, the corrosion resistance and wear resistance of the two sides of the copper sheet of the cooler are effectively enhanced by setting specific supersonic spraying process parameters and combining supersonic spraying powder.

[0017] (3) In this invention, the surface of the copper sheet used in the cooler is finally treated by PVD ion sputtering coating process, which is combined with the above-mentioned nickel-based laser cladding and supersonic spraying to carry out composite and multiple anti-corrosion treatment on the surface of the cooler, thereby improving the anti-corrosion and anti-wear performance of the copper sheet of the cooler and greatly extending the service life to more than 6 months. Detailed Implementation

[0018] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] In the description of this invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "inner", "outer", etc., indicate the orientation or positional relationship shown, and are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.

[0020] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0021] The present invention will be further described in detail below through specific embodiments and in conjunction with the embodiments. Example

[0022] A high-temperature anti-corrosion coating process for coolers used in fiberglass drawing in the glass fiber industry includes: (1) The edges of the copper sheets used in the cooler are treated with a nickel-based laser cladding process, specifically including: S1. Grind the surface of the copper sheet used in the cooler to remove the surface oxide scale and stains. Clean the surface with anhydrous ethanol and acetone, dry it, and protect the surface that does not require laser cladding. S2, The dried laser cladding powder is placed into the powder feeder and continuously fed using a coaxial powder feeding system to complete the laser cladding on the upper edge and adjacent side edges of the copper sheet, with a cladding thickness of 0.5mm. S3. The cladding coating is ground and polished, and the thickness of the coating after grinding is 0.4mm.

[0023] In this embodiment, the laser cladding process parameters are as follows: laser power is 1500W, scanning speed is 200mm / min, laser cladding powder feeding amount is 20g / min, protective gas is argon, and gas flow rate is 12L / min.

[0024] In this embodiment, the laser cladding powder comprises the following materials by weight percentage: Ni: 60%, Mo: 2.8%, Cr: 15%, Ti: 0.75%, Mn: 4%, with the remainder being Fe and unavoidable impurities, and the powder particle size is 150-450 mesh.

[0025] (2) The copper sheets used in the cooler are treated with a supersonic spraying process on both sides, specifically including: S1. Clean both sides of the copper sheet used in the cooler with anhydrous ethanol and acetone, and then dry it. S2. Place the dried supersonic spraying powder into the supersonic spraying equipment to complete the supersonic spraying, with a spraying thickness of 0.3 mm. S3. Use specialized grinding equipment to grind the sprayed surface smooth.

[0026] In this embodiment, the process parameters for supersonic spraying are: compressed air pressure 2MPa, propane pressure 0.5MPa, and nitrogen pressure 0.1MPa.

[0027] In this embodiment, the supersonic spray powder comprises the following materials by weight percentage: Ni: 60%, Cr: 20%, TIC and WC (ceramic phase): 20%.

[0028] (3) Finally, the surface of the copper sheet used in the cooler is treated with PVD ion sputtering coating process, specifically including: A PVD magnetron sputtering device was used to coat the surface of the cooler, with a coating thickness of 3 μm.

[0029] In this embodiment, the PVD magnetron sputtering coating uses a titanium aluminum nitride target.

[0030] In this embodiment, the operating parameters of the PVD magnetron sputtering equipment are as follows: vacuum degree is 0.3 × 10⁻⁶. -5 Torr, bias voltage 60V, target current 5A. Example

[0031] A high-temperature anti-corrosion coating process for coolers used in fiberglass drawing in the glass fiber industry includes: (1) The edges of the copper sheets used in the cooler are treated with a nickel-based laser cladding process, specifically including: S1. Grind the surface of the copper sheet used in the cooler to remove the surface oxide scale and stains. Clean the surface with anhydrous ethanol and acetone, dry it, and protect the surface that does not require laser cladding. S2, The dried laser cladding powder is placed into the powder feeder and continuously fed using a coaxial powder feeding system to complete the laser cladding on the upper edge and adjacent side edges of the copper sheet, with a cladding thickness of 0.6 mm. S3. The cladding coating is ground and polished, and the thickness of the coating after grinding is 0.5mm.

[0032] In this embodiment, the laser cladding process parameters are as follows: laser power is 1700W, scanning speed is 500mm / min, laser cladding powder feeding amount is 25g / min, protective gas is argon, and gas flow rate is 13L / min.

[0033] In this embodiment, the laser cladding powder comprises the following materials by weight percentage: Ni: 65%, Mo: 3%, Cr: 20%, Ti: 1.0%, Mn: 5%, with the remainder being Fe and unavoidable impurities, and the powder particle size is 150-450 mesh.

[0034] (2) The two sides of the cooler are treated with a supersonic spraying process, specifically including: S1. Clean both sides of the copper sheet used in the cooler with anhydrous ethanol and acetone, and then dry it. S2. Place the dried supersonic spraying powder into the supersonic spraying equipment to complete the supersonic spraying, with a spraying thickness of 0.35 mm. S3. Use specialized grinding equipment to grind the sprayed surface smooth.

[0035] In this embodiment, the process parameters for supersonic spraying are: compressed air pressure 2.5 MPa, propane pressure 0.7 MPa, and nitrogen pressure 0.2 MPa.

[0036] In this embodiment, the supersonic spray powder comprises the following materials by weight percentage: Ni: 65%, Cr: 15%, TIC and WC (ceramic phase): 20%.

[0037] (3) Finally, the surface of the copper sheet used in the cooler is treated with PVD ion sputtering coating process, specifically including: A PVD magnetron sputtering device was used to coat the surface of the cooler, with a coating thickness of 4 μm.

[0038] In this embodiment, the PVD magnetron sputtering coating uses a titanium aluminum nitride target.

[0039] In this embodiment, the operating parameters of the PVD magnetron sputtering equipment are as follows: vacuum degree is 0.5 × 10⁻⁶. -5 Torr, bias voltage 80V, target current 6A. Example

[0040] A high-temperature anti-corrosion coating process for coolers used in fiberglass drawing in the glass fiber industry includes: (1) The edges of the copper sheets in the cooler are treated using a nickel-based laser cladding process, specifically including: S1. Grind the surface of the copper sheet of the cooler to remove the oxide scale and stains. Clean the surface with anhydrous ethanol and acetone, dry it, and protect the surface that does not require laser cladding. S2, The dried laser cladding powder is placed into the powder feeder and continuously fed using a coaxial powder feeding system to complete the laser cladding on the upper edge and adjacent side edges of the copper sheet, with a cladding thickness of 0.7mm; S3. The cladding coating is ground and polished, and the thickness of the coating after grinding is 0.6mm.

[0041] In this embodiment, the laser cladding process parameters are as follows: laser power is 2000W, scanning speed is 800mm / min, laser cladding powder feeding amount is 30g / min, protective gas is argon, and gas flow rate is 15L / min.

[0042] In this embodiment, the laser cladding powder comprises the following materials by weight percentage: Ni: 70%, Mo: 5%, Cr: 15%, Ti: 1.2%, Mn: 6%, with the remainder being Fe and unavoidable impurities, and the powder particle size is 150-450 mesh.

[0043] (2) The two sides of the cooler are treated with a supersonic spraying process, specifically including: S1. Clean both sides of the copper sheet used in the cooler with anhydrous ethanol and acetone, and then dry it. S2. Place the dried supersonic spraying powder into the supersonic spraying equipment to complete the supersonic spraying, with a spraying thickness of 0.4 mm. S3. Use specialized grinding equipment to grind the sprayed surface smooth.

[0044] In this embodiment, the process parameters for supersonic spraying are: compressed air pressure 3MPa, propane pressure 1MPa, and nitrogen pressure 0.3MPa.

[0045] In this embodiment, the supersonic spray powder comprises the following materials by weight percentage: Ni: 75%, Cr: 12%, TIC and WC (ceramic phase): 13%.

[0046] (3) Finally, the surface of the cooler is treated with PVD ion sputtering coating process, specifically including: A PVD magnetron sputtering device was used to coat the surface of the cooler, with a coating thickness of 5 μm.

[0047] In this embodiment, the PVD magnetron sputtering coating uses a titanium aluminum nitride target.

[0048] In this embodiment, the operating parameters of the PVD magnetron sputtering equipment are as follows: vacuum degree is 0.8 × 10⁻⁶. -5 Torr, bias voltage 100V, target current 8A.

[0049] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A high-temperature anti-corrosion coating process for coolers used in fiberglass drawing, characterized in that: include: (1) The edges of the copper sheets used in the cooler are treated with a nickel-based laser cladding process, wherein the nickel-based laser cladding process specifically includes: S1. Grind the surface of the copper sheet used in the cooler to remove the surface oxide scale and stains. Clean the surface with anhydrous ethanol and acetone, dry it, and protect the surface that does not require laser cladding. S2. The dried laser cladding powder is placed into a powder feeder and continuously fed using a coaxial powder feeding system to complete laser cladding on the upper edge and adjacent side edges of the copper sheet. The cladding thickness is 0.5-0.8 mm. The laser cladding process parameters are: laser power 1500W-2000W, scanning speed 200-800mm / min, laser cladding powder feeding amount 20-30g / min, protective gas argon, and gas flow rate 12-15L / min. The laser cladding powder contains the following materials by weight percentage: Ni: 60-70%, Mo: 2.8-5%, Cr: 15-25%, Ti: 0.75-1.2%, Mn: 4-6%, with the remainder being Fe and unavoidable impurities. The powder particle size is 150-450 mesh. S3. The cladding coating is ground and polished, and the thickness of the coating after grinding is 0.4-0.6mm; (2) The two sides of the copper sheet used in the cooler are treated with a supersonic spraying process. The supersonic spraying process specifically includes: S1. Clean both sides of the copper sheet used in the cooler with anhydrous ethanol and acetone, and then dry it. S2. Place the dried supersonic spraying powder into the supersonic spraying equipment to complete the supersonic spraying. The spraying thickness is 0.3-0.4 mm. The process parameters for supersonic spraying are: compressed air pressure 2-3 MPa, propane pressure 0.5-1 MPa, and nitrogen pressure 0.1-0.3 MPa. The supersonic spraying powder contains the following materials by weight percentage: Ni: 60-75%, Cr: 10-20%, TIC and WC: 10-20%. S3. Use specialized grinding equipment to grind the sprayed surface smooth; (3) The surface of the copper sheet used in the cooler is treated with PVD ion sputtering coating process.

2. The high-temperature anti-corrosion coating process for a cooler used in fiberglass drawing according to claim 1, characterized in that: The PVD ion sputtering coating process specifically includes: A PVD magnetron sputtering device was used to deposit a film on the surface of the copper sheet used in the cooler, with a film thickness of 3-5 μm.

3. The high-temperature anti-corrosion coating process for a cooler used in fiberglass drawing according to claim 2, characterized in that: The PVD magnetron sputtering coating uses a titanium aluminum nitride target.

4. The high-temperature anti-corrosion coating process for a cooler used in fiberglass drawing according to claim 2, characterized in that: The operating parameters of the PVD magnetron sputtering equipment are as follows: vacuum degree is 0.3 × 10⁻⁶. -5 ~0.8×10 -5 Torr, bias voltage 60-100V, target current 5-8A.

Citation Information

Patent Citations

  • Supersonic spray coating method of crystallizer copper plate

    CN101302619A

  • Pipeline based on inner wall thermal spraying and laser cladding remanufacturing and preparation method thereof

    CN109881194A